The Effects of Fun Active Learning and Visualization Strategies on EFL Students’ Speaking Skills: A Quasi-Experimental Study in an Indonesian Senior High School - Atalisi Zalukhu; Fitria Rahmawati; Mariska Intan Sari; Aliya Noor Cahyani (Faculty of Education and Teacher Training of UIN Palopo, 2026)
The goal of this study was to look at speaking problems among secondary school students by closely watching how their speaking skills grew during the learning process. This study used a collaborative classroom action research method, where the researchers worked together with the Year 11 English teacher at SMA N 8 Medan instead of doing the research on their own. Before the test, the average score was 58.65, but after the test, it went up to 73.78. These results show that students' speaking skills improved a lot after using the narrative approach. When comparing the scores before and after the teaching strategies were used, there was a big difference in how well the students performed. The data analysis supports the first research question by showing that using visualization tactics really helps improve the speaking skills of students at SMA N 8 Medan. More research shows that visualization tactics help students get better at speaking, as seen from the increase in scores from 55 to 96. Comparing the pre-test and post-test scores shows a big difference in student performance before and after applying the teaching strategies. The results of the data analysis confirm the first research question by showing that using visualization tactics effectively improves the speaking skills of students at SMA N 8 Medan. Further research shows that visualization tactics help students improve their speaking skills, as seen from the increase in scores from 55 to 96.